Development of a gamification-based program to support ESD competency improvement in botanical gardens - Saefudin, Saefudin; Kusnadi, Kusnadi; Hastika, Asyah Dwi; Zidan, Zuliande (JURNAL BIOEDUKATIKA, 2024)
The Sustainable Development Goals, particularly Goal 4, have been developed and implemented by various educational institutions around the world. As an agent of development, the Indonesian University of Education (UPI)  has the potential to develop and implement ESD, especially through the use of UPI botanical garden. The purpose of this study is to develop a program and measure its effectiveness in terms of  ESD capacity and ecotourism potential. This research is a development study using the ADDIE approach in which 74  teacher candidates participated. Program development was successfully implemented by creating: (1) 5 learning resource posts; (2) Botanical ECO gamification learning flow;  (3) 5 practical activities; (4) five games that integrated gamification elements; (5) Botanical ECO-Gamification Guidebook; and (6) Instruments to evaluate program effectiveness in terms of ESD competencies and conceptual mastery. The research results showed that the developed instrument  had high validity and reliability, and was suitable for use (19 items). The Botanical ECO gamification program was rated in the good category for improving collaboration competency (80,41)  and in the good category for self-awareness competency (78,77). The implementation of the Botanical ECO gamification program to develop ESD was rated as very well received by students (85.81). The program was rated as excellent (82,17) or eligible of being one of the ecotourism programs on the UPI campus.